STUDY ON THE EFFECTIVENESS OF ACTIVATED CARBON FOR REDUCING HARDNESS AND IRON (FE) CONTENT IN WELL WATER - Fajar, Mutiara; Angreni Limbong, Ruth; Utami, Resarizki (Department of Environmental Engineering (Prodi Teknik Lingkungan), Fakultas Sains dan Teknologi, UIN Ar-Raniry Banda Aceh, 2024)
One source of clean water for communities is well water, which originates from groundwater. Groundwater typically has higher hardness levels compared to surface water and contains iron, as it percolates through rocks and subsurface soil. To address the issue of hardness and iron content in well water, one effective method is the adsorption process using activated carbon. This study investigates the effectiveness of activated carbon in reducing both hardness and iron (Fe) concentrations in water. The research tested different carbon thicknesses (60 cm, 70 cm, and 80 cm) to assess their impact on reducing hardness and iron (Fe) levels. The initial hardness level was 580 mg/l, and the iron (Fe) content was 2.08 mg/l. After treatment with activated carbon, the reduction in hardness at thicknesses of 60 cm, 70 cm, and 80 cm was 69.31%, 77.13%, and 82.87%, respectively. The reduction in iron (Fe) content at these thicknesses was 92%, 96%, and 97%, respectively. The results indicate that increased thickness of the activated carbon improves its effectiveness in reducing both hardness and iron (Fe) levels. As the thickness of the activated carbon increases, its efficiency in treating water also increases, showing that thicker layers of activated carbon enhance processing effectiveness.